Meta-Analysis of the Effectiveness of Using Antiplatelet Drugs Uptake in Decreasing Mortality in COVID-19 Patients - Nurhayati, Happy; Pamungkasari, Eti Poncorini; Murti, Bhisma (Indonesian Journal of Medicine, 2021)
Background: Viscoelastic coagulation testing in COVID-19 patients often found elevated concentrations of D-dimer and fibrinogen. Thrombotic complications can be in the form of Venous Thromboembolism (VTE), where this thrombotic disease is one of the factors associated with increased mortality of COVID-19 patients. This study aims to analyze the effectiveness of antiplatelet drugs in reducing mortality in COVID-19 patients.Subjects and Method: This is a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2020-2021 using PubMed, Science Direct, Google Scholar, and Scopus databases. The article search was carried out by considering the eligibility criteria defined in the PICO model. Population= COVID-19 patients, Intervention= using antiplatelet drugs, Comparison= not using anticoagulant drugs, Outcome= mortality. The keywords used were "antiplatelet" AND "mortality" AND "COVID-19". The inclusion criteria used were English full-text cohort papers and the relationship measure used as the adjusted odds ratio (aOR). Based on the database, 9 articles fulfilled the inclusion criteria. The analysis was carried out using RevMan 5.3 software.Results: The meta-analysis was carried out on 9 articles from the UK, Spain, Germany, Poland, America, Israel, and China. The results of data processing showed that COVID-19 patients who received antiplatelet drugs had a 0.70 times risk of dying than those without antiplatelet drugs, and it was not statistically significant (aOR= 0.70; CI 95%= 0.46 to 1.07; p= 0.100).Conclusion: The use of anticoagulant drugs reduces the mortality risk of COVID-19 patients, but it is not statistically significant.Keywords: antiplatelet, mortality, COVID-19Correspondence: Happy Nurhayati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: happyajja3@gmail.com. Phone: +62 81226160538.Indonesian Journal of Medicine (2021), 06(03): 315-324https://doi.org/10.26911/theijmed.2021.06.03.09